Pengaruh Gibberellin (GA4) terhadap Waktu Perkecambahan dan Pertumbuhan Tinggi Semai Cendana (Santalum Album Linn.) - Asri Insiana Putri; Toni Herawan (Jurnal Ilmu Kehutanan, 2008)
Effect of Gibberellins (GA4) on Germination Time and Height of Cendana (Santalum album Linn.) The hemiparasite Santalum album Linn. (cendana) grows very slow, in nature the rare and difficult seeds need stimulation to germinate. Gibberellins (including GA4) are growth regulators, usually used to increase growth as well as to break seed dormancy. The objectives of this research were to investigate the influence of gibberellins on germination percentage and height of cendana growth. Experiment was laid out in a Completely Randomized Design with 3 replicates of 300 seeds for germination percentage and 3 replicates of 10 seeds for seedling growth. Gibberellin was applied as treatment with 100, 300, and 500 ppm. The seed germination was recorded until 9 weeks, and height of plants measured until 8 months at the greenhouse. The results showed that the addition of gibberellins at all treatment increased the percentage of germination and caused the seeds germinated four weeks earlier than the control. In the first 4 months, 500 ppm gibberellins gave the highest acceleration of germination, afterward all treatments have relatively the same influences. Gibberellins gave positive effect on height of cendana growth. After 7 months, the growth decreased although all gibberellin treatments gave higher growth than the control.